138k views
4 votes
Help asap thank you!!!

Help asap thank you!!!-example-1
User Ssz
by
5.7k points

1 Answer

4 votes

Hi there! :)

Answer:

The good answer is the top left one, which is:

2x -1(5 - 3x) = 4x +2

2x - 5 + 3x = 4x + 2


Explanation:

2x - 1(5 - 3x) = 4x + 2

The correct first step is to distribute the "-1" to the entire parentheses:

-1 × 5 = -5

-1 × -3x = 3x

Once this first step is done, you are left with an equation looking like this:

2x - 5 + 3x = 4x + 2

Which is the top left answer for you!


There you go! I really hope this helped, if there's anything just let me know! :)

User Zovits
by
5.6k points